Accountability and Incumbent Re-election in Indonesian Local Government - Yuliati, Retno; Raharjo, Soemarso Slamet; Siswantoro, Dodik (Universitas Prasetiya Mulya, 2016)
This paper examines the relationship of financial and performance accountability towards incumbent re-election in Indonesian local election. Sample of this research is 56 regencies and cities that held local election with an observation period of 2011 until 2013. Audit opinion and audit finding data are used to measure financial accountability; meanwhile the performance score and evaluation of performance accountability are used as proxy of performance accountability. The analysis shows that higher audit finding of the weakness of internal control system decrease the probability of re-election and higher performance score increase the probability of re-election. In contrast, audit opinion, audit finding of non-compliance to the regulation and legislation, and evaluation of performance accountability have no relationship with the probability of incumbent re-election.